Legal Dynamics in the Vidi Aldiano Case: A Review of Conflict of Interest and Intellectual Property Rights - Syarah Syam Amir; Nurul Insi Syahruddi (Cita konsultindo, 2026)
The copyright infringement case involving the singer Vidi Aldiano has drawn significant attention within the study of intellectual property law in Indonesia, particularly regarding conflicts of interest between creators, rights holders, and actors in the music industry. This study aims to analyze the legal dynamics that arise in the context of copyright disputes and conflicts of interest based on the prevailing laws and regulations in Indonesia. The research employs a doctrinal or normative legal approach with qualitative analysis of secondary data, including legislation, legal documents, news reports, and relevant public statements.The findings indicate that weaknesses in collective management systems and the lack of transparency in royalty administration constitute major triggers of conflict. Moreover, the blurred boundaries between personal, professional, and institutional interests within the music industry further complicate dispute resolution. This study recommends strengthening regulatory frameworks, enhancing legal protection for copyright holders, and increasing transparency within collective management organizations in the collection and distribution of royalties. These insights are expected to serve as a reference for policymaking and for future reform of Indonesia’s intellectual property law.